SISTEM PENDUKUNG KEPUTUSAN PEMILIHAN AIR MINUM ISI ULANG TERBAIK DAERAH MEDAN MARELAN - Muhardi Saputra (Jurnal Teknovasi : Jurnal Teknik dan Inovasi, 2020)
Poor taste or time efficiency in boiling water or regulations in making drill water make people prefer to choose refill drinking water for their daily drinking needs. So that the proliferation of refill drinking water businesses gave rise to the author's idea to make a research about which businesses have the best quality water. The goal is that people get water that is healthy and good for the body. Getting the best and healthiest water is a right for the community. This study uses a decision support system with the simple additive weighting (SAW) method to manage the criteria in order to get the best decision. The research area is the refill drinking water business in Medan Marelan Pasar V. The criteria used in the assessment of water are odor, taste, color, pH and hardness.And the researchers selected 3 refill drinking water businesses from the number of drinking water refill businesses in the Marelan field area. Because these 3 businesses are well known in the Medan area, Marelan also has branches in other areas and has a Yamaha brand filter engine. So that it is trusted by the surrounding community. The results of the study concluded that of the 3 businesses there was one refill drinking water business in the Medan Marelan area which had the highest value of 0.8733. So it is worth recommending to the surrounding community to do refill drinking water in only that business.